PENGARUH APLIKASI STRATEGI JUST IN TIME TERHADAP EFEKTIVITAS DAN EFISIENSI BIAYA PRODUKSI PADA PT. SANTOSA JAYA ABADI SIDOARJO - Rahayu Rahayu (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
Just in time (JIT) is one of concepts that support cost management to anticipate the change that happens in industrial environment because of the advance of technology and automation. In a concept, JIT doing cost elimination through elimination of inventory number (inventory equals 0). This elimination of inventory number automatically lost the cost of storage and transportation, and cause the decrease of tolerate level toward product error. The aim of this research is to know and examine the influence factors of purchase, production, material shipment, product shipment and JIT environment simultaneously that have significant influences toward the cost production’s effectively and efficiently at PT. Santosa Jaya Abadi Sidoarjo, and also to know and examine the dominant influence factors of purchase, material shipment, product shipment, and JIT environment toward cost production’s effectively and efficiently at PT. Santosa Jaya Abadi Sidoarjo. The result of analysis shows that the first hypothesis that proposed in this research that is, “it is factors of purchase, production, and material shipment, product shipment, and JIT environment simultaneously have significant influence toward the cost production’s effectively and efficiently at PT. Santosa Jaya Abadi Sidoarjo” is accepted. This is supported by the result of F-test, in which the result shows that Fcount (14.521) > Ftable (3.13). By seeing on the value of R square = 0.729, it means that the up-down variation of Y variable (cost production’s effectively and efficiently at PT. Santosa Jaya Abadi Sidoarjo) as much as 72.9% is influenced by all independence variable in model and the rest as much as 27.1% is stipulated by  variable out side of model. It means that the contribution of independence variables in model is good enough because it is more than 50%. Beside this, there are many variables that influences the effectively and efficiently of cost production at PT. Santosa Jaya Abadi Sidoarjo that not examined in this research. The second hypothesis, that is, “JIT environment have dominant influence toward the cost production’s effectively and efficiently at PT. Santosa Jaya Abadi Sidoarjo” is accepted. This is supported by the result of t-test which is the value of tcount is 4.735, and ttable is 1.96, so that tcount > ttable. Beside this, the dominant influence can be stipulated with the highest value of r2 for JIT environment factor, that is, as much as 0.00476.